Enhancing Thermal and Mechanical Properties of UHMWPE/HA Composite as Tibial Tray - Yusuf Bramastya Apriliyanto; Sri Sugiarti; Sulistioso Giat Sukaryo (Indonesian Journal of Chemistry, 2020)
A bearing material in an artificial knee joint has to have good thermal and mechanical properties to prevent wear in order to be used as a tibial tray. Despite its well-known good properties, ultrahigh molecular weight polyethylene (UHMWPE) still needs to be modified to enhance its physical strength in its use in artificial joints. In this research, composites made from UHMWPE and hydroxyapatite (HA) were prepared by mechanical alloying and hot press method and their thermal and mechanical properties were modified using gamma rays. The composites were prepared using various HA loading ratios and irradiated using gamma rays at doses of 0, 25, 50, and 75 kGy. The effects of HA loading and gamma irradiation on thermal and mechanical properties were studied by various methods. The results showed that the addition of HA enhanced the hardness of UHMWPE by 8–15% and the maximum stress up to 38%. Gamma irradiation enhanced the crystallinity by 113–172%, the melting point by 0.6–0.7%, and decreased the break elongation of composites by 23–48%. Addition of polyvinyl alcohol (5% w/w) in composites reduced their rigidity by 16–47% and hardness by 3–9%.